(untitled) (Research, Society and Development, 2022)
Objective: The present study aims to analyze the scientific evidence about childhood food neophobia, gathering data on the influence of childhood food neophobia on nutritional status and its repercussions over time. Method: This is an integrative literature review where articles were selected on Google Scholar, VHL, PubMED, LIACS and SciELO platforms from 2017 to 2022. The inclusion criteria used were original articles, indexed in the databases selected in the Portuguese and English languages. The exclusion criteria were publications of theses, monographs, conference proceedings and dissertations, which did not adhere to the theme. The descriptors used were in Portuguese "neophobia", "food neophobia", "food introduction", "child food neophobia", "eating disorder", "child nutrition", "food habit" and "food preference" and in English. “neophobia”, “food neophobia”, “introduction to feed”, “child food neophobia”, “eating disorders”, “infant nutrition”, “eating habits” and “Food preferences”. Conclusion: Thus, the present study showed significant differences in some domains of eating behavior among children and adolescents in the samples presented, however, no differences were found in relation to food neophobia. The studies showed that children had a lower intake of red fruits, vegetables, legumes and fish, as well as an increase and frequency of consumption of peas and beans. Food neophobia does not only exist in Brazil, but also in other countries and at different ages, and can have repercussions throughout life.